Semantic Features of Visual Verb - Asadovna, Adilova Mukhabbat; Bahodirivich, Berdimurodov Murodjon (European Journal of Life Safety and Stability (2660-9630), 2021)
The problem of understanding the meaning has always occupied a central place in every semantic theory and largely determined the object and goals and research methodology. In traditional semantics, the concept of the meaning of a linguistic sign is adopted, which is characterized by many linguists as classical. It is based on the understanding of the word as a sign that has a plan of expression (signifier) and a plan of content (signified) and correlates with the denotation (referent), which is called the word.